(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
Work in Islamic law based on the Qur’an and Hadith, is an obligation and has the right to get a job. The Qur’an is very opposed to acts of lazy, wasting time, and not doing things that are not productive. Someone must work to work as well as possible to get his salary, while for employers must pay a decent wage, in recognition of the work performance of workers. The national wage system is regulated in Act Number 13 Year 2003 about Manpower, from the aspect of formalities, has guaranteed the rights and obligations of workers and employers. But from the substance aspect, workers are paid cheap wages for various reasons. To achieve a decent wage for productive workers, it must be supported by good, harmonious and moral cooperation between employers and workers. Both parties are one entity in carrying out workers, not as parties with training positions. Standards for both parties, in addition to national law, also adhere to Islamic values ??based on the Qur’an and Hadith.